Combustion and Emission of Castor Biofuel Blends in a Single-Cylinder Diesel Engine - Fangyuan Zheng; Haengmuk Cho (Energies, 2023)
Fossil fuels confront the problem of strategic resource depletion since they have been continuously utilized for more than 200 years and cause serious damages to the ecological environment of the planet. In this work, the transesterification of castor plant oil was utilized to make biodiesel, and castor biodiesel’s physicochemical qualities were assessed. On a single-cylinder, four-stroke, water-cooled agricultural diesel engine, an experimental study was conducted to compare and analyze the engine performance and emission characteristics of diesel and biodiesel blends in various amounts. The B20, B40, B60, and B80 biodiesel blends were evaluated at different engine speeds (1200, 1400, 1600, and 1800 rpm) with a constant engine load (50%). According to the experimental findings, the brake thermal efficiency (BTE) declines as the engine speed rises, and the biodiesel fuel blend has a lower brake thermal efficiency (BTE) than diesel fuel because of its higher density and viscosity and lower calorific value. The amount of gasoline required to create power increases as the speed does, and the brake-specific fuel consumption (BSFC) trend is upward. Due to their low calorific value and high viscosity properties, biodiesel blends have a greater brake-specific fuel consumption (BSFC) than diesel. The fuel’s exhaust gas temperature (EGT) has an upward trend with an increased rotational speed. The biodiesel blend’s high cetane number shortens the ignition delay and lowers the exhaust gas temperature (EGT) compared to diesel. A fuel with oxygen added, biodiesel enhances combustion, increases the combustion temperature, speeds up the oxidation process, and lowers carbon monoxide (CO) and hydrocarbon emissions. B80 produces the lowest carbon monoxide and hydrocarbon emissions at 1800 rpm, at 0.33%, and 30 ppm, respectively. On the other hand, increased carbon dioxide (CO2) emissions result from a high oxygen concentration. In addition, compared to diesel fuel, biodiesel’s greater combustion temperature causes the creation of increased nitrogen oxide (NOx) emissions. According to the research findings, a castor biodiesel fuel blend is an excellent alternative fuel for engines since it can be utilized directly without modifying the current engine construction and has good engine and exhaust emission performance.